2012
DOI: 10.3109/08039488.2012.665080
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–behaviour group therapy for men voluntary seeking help for intimate partner violence

Abstract: All kinds of self-reported partner related violence were significantly reduced by treatment, but being on a waiting list for 4 months did not reduce violent behaviour compared with those immediately receiving treatment. The results indicate that that the group treatment had an effect in itself beyond the wish and intention from the men to reduce their partner violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 9 publications
1
58
0
6
Order By: Relevance
“…The treatment self‐help manual, consisting of 219 pages divided into eight modules, was informed by CBT protocols for interpersonal violence (Heyman & Schlee, ; Murphy & Eckhardt, ; Palmstierna, Haugan, Jarwson, Rasmussen, & Nøttestad, ) and emotion dysregulation (Fruzzetti, ; McKay, Wood, & Brantley, ). All modules contained homework exercises.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment self‐help manual, consisting of 219 pages divided into eight modules, was informed by CBT protocols for interpersonal violence (Heyman & Schlee, ; Murphy & Eckhardt, ; Palmstierna, Haugan, Jarwson, Rasmussen, & Nøttestad, ) and emotion dysregulation (Fruzzetti, ; McKay, Wood, & Brantley, ). All modules contained homework exercises.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to the moralistic attitude in CBT programs that has components from the Duluth Model [2]. The previous report [4] showed that a 15-week manual, group-based CBT program significantly and substantially reduced self-reported violent behavior at the end of treatment.…”
Section: Discussionmentioning
confidence: 83%
“…A study of the Brøset Model [4] showed that a 15-week manual, group-based CBT program significantly and substantially reduced self-reported violent behavior. After the initial assessment but before group therapy sessions, 26 men were randomly selected for immediate treatment or put on a waiting list.…”
Section: Introductionmentioning
confidence: 99%
“…For both trials (Kistenmacher, 2000;Palmstierna et al, 2012), around 70% of the men used substances.…”
Section: Standalone Ipv Interventionsmentioning
confidence: 99%
“…Of the final two trials, one used MI in targeting IPV and SU simultaneously (Mbilinyi et al, 2011), while the other used MI in targeting IPV alone (Kistenmacher, 2000). Kistenmacher (2000) and Palmstierna et al (2012) included samples where 66.7% and 77% of the samples, respectively, were considered 'hazardous drinkers' 1 or dependent on alcohol. Kistenmacher Identification Test (AUDIT) (Murphy et al, 2018;Stuart et al, 2013) and the Short Inventory of Problems (SIP; Miller, Tonigan & Longabaugh, 1995) (Stuart et al, 2013).…”
Section: Study Selectionmentioning
confidence: 99%